Knowledge in Dialogue, a networked continuing education program: University and basic education - Silva, Gilberto Ferreira; Aquino Machado, Juliana (Education Policy Analysis Archives, 2020)
This study analyzes the actions and principles that emerged in the development of a continuing education project in a municipal school network, in light of the decolonial perspective, as a possibility of thinking about the processes from a geoepistemic place. This movement presupposes evidencing the processing of constructions and formative experiences from the perspective of teachers, exercising other ways of producing meanings, forms of understanding and knowledge. In the dialogue between universities, through collaboration with a postgraduate program in education and basic education, the main principles that lead to develop a proposal of in-service training built with the network. Based on the syntheses produced, it is evident the role of educators as teacher-intellectuals, in the production of pedagogical knowledge proper to the field of professional activity, in the creation of a privileged space of knowledge sharing and knowledge production, as well as recognizing an essentially collaborative movement among teachers, ensuring membership by voluntary adherence to the proposal.